PENGARUH RASIO LIKUIDITAS, RASIO LEVERAGE DAN RASIO NILAI PASAR TERHADAP RETURN SAHAM PADA PERUSAHAAN FOOD AND BEVERAGE YANG ADA DI BURSA EFEK INDONESIA - Abdurrohman Abdurrohman; Anis Fuad Salam; Fitria Haquei; Elis Badariah; Imat Hikmat (LP2M Universitas Bina Bangsa, 2024)
This research aims to determine the effect of liquidity ratios, leverage ratios and market value ratios on stock returns, either partially or simultaneously. Researchers limit the problem to only one type of ratio for each variable in this research, namely the liquidity ratio proxied by the Current Ratio (CR), the leverage ratio proxied by the Debt to Equity Ratio (DER) and the market value ratio proxied by Earning Per Share (EPS). This research uses quantitative methods with the research object being food and beverage companies listed on the Indonesian Stock Exchange for the 2018-2022 period. The sample used in this research was 9 companies using purposive sampling techniques. Data analysis uses multiple linear regression methods which are processed using SPSS. The results of hypothesis testing show that H1 the liquidity ratio as proxied by CR has a significant effect on stock returns as indicated by the tcount > ttable value (2.130 > 2.01954) with a significance level of 0.039 < 0.05. H2: The leverage ratio proxied by DER has no significant influence on stock returns as proven by tcount < ttable value (-1.344 < 2.01954) with a significance level of 0.186 > 0.05. H3 The market value ratio proxied by EPS has a significant effect on stock returns, this is indicated by the tcount > ttable value (4.668 > 2.01954) with a significance level of 0.00 < 0.05. Furthermore, H4, simultaneously the liquidity ratio proxied by CR, the leverage ratio proxied by DER and the market value ratio proxied by EPS have a significant effect on stock returns, this is shown by Fcount > Ftable value (9.738 > 2.833) with a significance level below 5% (0.00 < 0.05).